Autism spectrum symptoms in Smith-Magenis syndrome and Williams syndrome: comparisons and contrasts - Osório, Ana Alexandra Caldas (2015)
Objectives: Genetic syndromes with distinctive cognitive and behavioural phenotypes - such as Smith-Magenis syndrome (SMS) and Williams syndrome (WS) - offer unique opportunities to explore the links between specific genes and neurodevelopmental disorders. While some studies have reported the occurrence of autistic symptoms in SMS, evidence for such symptomatology in WS is scarcer. This study is the first to compare and contrast levels of autistic symptoms in SMS and WS.Methods: Parents/caregivers of 11 individuals with SMS and 14 individuals with WS completed the Social Communication Questionnaire.Results: Results indicate that both syndromes present, albeit in distinct degrees, behavioural signs of the autistic spectrum. The SMS group scored significantly higher on both current and lifetime symptoms. The mean lifetime form score of the SMS group (particularly males) was consonant with the presence of an autism spectrum disorder. Regarding the WS group, even though the mean score was below the clinical threshold, it was still above what has been reported in typically developing samples.Conclusion: Our study contributes to a better definition of the neurobehavioural profiles of SMS and WS, as it offers comparisons and contrasts that may, in turn, prove beneficial for early diagnosis and intervention.